Peer Assessment for Construction Management and Quantity Surveying Students - Patricia McLaughlin (Construction Economics and Building, 2012)
Students undertaking the Bachelor of ConstructionManagement degree course at RMIT University, Melbourne,qualify for registration with the Australian Institute ofQuantity Surveyors (AIQS) and the Australian Institute ofBuilding (AIB) upon graduation. Over the past decade thedegree course has been constantly upgraded and altered inline with recommendations from professional bodies such asthese and other industry partners. In 1994 the Departmentof Building and Construction Economics re-assesseda range of subjects including the first year technologysubjects. Out of the review a problem-based integratedlearning unit was developed and tested. This unit has nowbeen in place for ten years.Quantity surveying and construction management likemost other professions in the construction industryrequire teamwork and advanced consultation skills. Theseskills may be learnt through experience but there isconsiderable evidence that these skills can be taught in theundergraduate years. Therefore in line with team-basedapproaches used in industry and professional constructionsettings, this year a new assessment model - peerassessment - will be applied to the problem-based learningunit. This paper describes the procedures and processesused to introduce the change and examines the theoreticalbase upon which the model was developed.